Characterization and Development of Edible Film/Coating from Lesser Yam Starch-Plasticizer Added with Potassium Sorbate or Cinnamon Oil in Affecting Characteristics and Shelf Life of Stored, Coated Strawberry - Wilbur Donald Raymond Pokatong; Jessica Decyree (Reaktor, 2018)
Starch of lesser yam (‘gembili’ in Indonesian) has been used as a base for edible film and coating. Potassium sorbate and cinnamon oil are known as strong antimicrobial agents. This research was aimed to investigate the physical and mechanical characteristics of edible film from lesser yam starch-plasticizer formulations added with potassium (K) sorbate or cinnamon oil and its application as coating to strawberries. Incorporation of either K-sorbate or cinnamon oil at higher concentration resulted in reduced tensile strength and elongation with higher water vapor transmission rate (WVTR). The selected edible film formulations were applied as coating on strawberry stored at two conditions: room (28-30°C) and refrigeration temperature (5-6°C). At room temperature, controls had shelf life only for 2 and 4 days and strawberries coated with addition of K-sorbate lasted for 5-6 days, and those with addition of cinnamon oil prolonged for 5-11 days. At refrigeration storage, shelf life of controls was 9 and 18 days whereas K-sorbate-added formulations further prolonged shelf life of strawberries for 19-21 days, and those added with cinnamon oil lasted for 25-26 days. Therefore, all coated, stored strawberries had longer shelf life and more retained strawberries’ quality including lower weight loss, higher hardness, and lower microbial count.Keywords: cinnamon oil; edible coating; edible film; potassium sorbate; strawberry